Importazione e distribuzione delle anfore San Lorenzo 7 nella Cisalpina occidentale - Lorenzatto , Anna; QUIRI, ELENA; Monticone , Alessia (Rei Cretariae Romanae Fautorum Acta, 2024)
The large number of San Lorenzo 7 amphorae found in Piedmont and Valle d’Aosta allows hypothetically to place their production in the northern Aegean and/or Istro-Pontic area. These amphorae seem to be coherent with economic and commercial dynamics in the Po valley and in the Alpine area during the Middle and Late Roman Empire. As the others eastern amphorae, the San Lorenzo 7 revolve around the Po-Adriatic axis. The ports of the upper Adriatic are used to the sorting of merchandise; furthermore, the amphoras go up the river Po to west Cisalpina (Torino) and the surrounding valleys, along the courses of the tributaries of the Po, reaching northern and western Alpine passes (Ivrea and Aosta, Vercelli, Cavour) to the Transalpine provinces. The contexts of Turin and Cavour, where San Lorenzo 7 were reused as cineraries, confirm their diffusion between the 2nd and the 5th century AD.